Green–Solvent–Processable Perovskite Solar Cells. Issue 2 (20th November 2020) - Cui, Yuying; Wang, Shurong; Ding, Liming; Hao, Feng
Abstract : Organ–inorganic hybrid perovskite solar cells (PSCs) have attracted extensive attention with a certified power conversion efficiency (PCE) beyond 25% due to their superior photoelectric properties. However, most reported high‐efficiency PSCs are fabricated with toxic solvents, which raises a major obstacle for potential commercialization. Herein, the recent research progress of green solvents for high‐efficiency PSCs is summarized from antisolvents, precursor solvents, and solvents for electron/hole transport materials, aiming to promote the development of green solvents for PSCs and meet the requirement of sustainable development of the PSCs field. Future challenges and prospects are also discussed to expedite the rational design of green‐solvent‐processed PSCs. Abstract : Organic−inorganic hybrid perovskites solar cells (PSCs) have attracted worldwide attention, however, most of them have been manufactured using volatile and highly toxic solvents, which is a major obstacle to the large‐scale implementation. This article summarizes the recent progress of green solvents in the fabrication of efficient PSCs, and the future prospects are discussed.